"Why" or "how": the effect of concrete versus abstract processing on intrusive memories following analogue trauma - White, R; Wild, J (Elsevier, 2016)
Emergency service workers, military personnel, and journalists working in conflict zones are regularly exposed to trauma as part of their jobs and suffer higher rates of posttraumatic stress compared with the general population. These individuals often know that they will be exposed to trauma and therefore have the opportunity to adopt potentially protective cognitive strategies. One cognitive strategy linked to better mood and recovery from upsetting events is concrete information processing. Conversely, abstract information processing is linked to the development of anxiety and depression. We trained 50 healthy participants to apply an abstract or concrete mode of processing to six traumatic film clips and to apply this mode of processing to a post-training traumatic film. Intrusive memories of the films were recorded for 1 week and the Impact of Events Scale - Revised (IES-R; Weiss and Marmar, 1997) was completed at 1-week follow-up. As predicted, participants in the concrete condition reported significantly fewer intrusive memories in response to the films and had lower IES-R scores compared with those in the abstract condition. They also showed reduced emotional reactivity to the post-training film. Self-reported proneness to intrusive memories in everyday life was significantly correlated with intrusive memories of the films, whereas trait rumination, trait dissociation, and sleep difficulties were not. Findings suggest that training individuals to adopt a concrete mode of information processing during analogue trauma may protect against the development of intrusive memories.